2016
DOI: 10.1007/s11606-015-3562-5
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Stroke Meaningful Use Measures in a National Electronic Health Record System

Abstract: BACKGROUND:The Meaningful Use (MU) program has increased the national emphasis on electronic measurement of hospital quality. OBJECTIVE: To evaluate stroke MU and one VHA stroke electronic clinical quality measure (eCQM) in national VHA data and determine sources of error in using centralized electronic health record (EHR) data. DESIGN: Our study is a retrospective cross-sectional study of stroke quality measure eCQMs vs. chart review in a national EHR. We developed local SQL algorithms to generate the eCQMs, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…26 In the Veterans Health Administration integrated health system, the final version of a Meaningful Use program eCQM regarding stroke had nearly 90% accuracy when local algorithms were iteratively improved by examining patterns of misclassifications. 20 These studies illustrate that although significant challenges exist with eCQM implementation, mature data systems that iteratively examine and address measure misclassifications can achieve high levels of accuracy. However, this customization is often time-consuming and requires specialized informatics expertise.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…26 In the Veterans Health Administration integrated health system, the final version of a Meaningful Use program eCQM regarding stroke had nearly 90% accuracy when local algorithms were iteratively improved by examining patterns of misclassifications. 20 These studies illustrate that although significant challenges exist with eCQM implementation, mature data systems that iteratively examine and address measure misclassifications can achieve high levels of accuracy. However, this customization is often time-consuming and requires specialized informatics expertise.…”
Section: Introductionmentioning
confidence: 96%
“…Studies examined the feasibility and accuracy of eCQMs in pediatrics, 16 asthma, 17 cancer, 17,18 diabetes, 17 coronary heart disease, 19 cardiovascular disease, 20,21 and in primary care and preventive health screening. 17,21 Not surprisingly, many of these studies reported challenges with data extraction and accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Phipps and colleagues developed and validated inpatient stroke electronic clinical quality measures that are part of the Meaningful Use (MU) program and VA efforts to improve inpatient stroke care. 1 The authors found that stroke MU indicators can be accurately generated from existing VA data in its electronic health record (EHR) system (nearly a 90 % match to chart review), but accuracy decreased slightly when data from the VA's national-level corporate data warehouse (CDW) was used rather than more complete local data sources. The authors also found that a relatively small number of error types are responsible for a large number of the observed mismatches, suggesting specific areas in which EHR developers and informaticians could improve the accuracy of the electronic record for generating MU measures.…”
mentioning
confidence: 99%
“…There have been relatively few studies on the accuracy of eCQMs. Therefore, the report by Phipps 8 and colleagues in this issue of JGIM offers encouraging results that such measures can be implemented and will yield accurate results. However, this study was conducted only within VA hospitals using a single EHR, and there may be differential accuracy of eCQMs across different EHRs.…”
Section: Advance Measurement Of Care Processesmentioning
confidence: 95%